Poetic dialect of the English language : a grammar and lexicon of words and forms of speech peculiar to English poetry - Hale, Horatio, 1817-1896.
Eight volumes of a manuscript concerning the grammar and lexicon of words and forms of speech in English poetry. Includes an introductory essay entitled "The Poetic Dialect" and an appendix entitled "Aristotle on Poetic Diction.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Lawyer and enthnologist. Full name: Horatio Emmons Hale.
Collection material in English.
Keywords: Poetry; Ethnologists; Lawyers